Enjoy our universe : you have no other choice - De Rújula, A. (Alvaro) (Oxford University Press, 2018)
A richly illustrated book on fundamental physics, cosmology, black holes, Higgs bosons, and time travel for a wide audience. This guide for an enjoyable visit to the Universe is humorous but not a joke. It establishes clear distinctions between things we know for sure and things that we know we do not know. In this sense, it is scientifically honest.